P66 Characterization of the pharmacokinetics of acetaminophen and its metabolites in the fetus through integration of placental transfer in a physiologically based pharmacokinetic model. Issue 6 (17th May 2019) - Mian, P; Allegaert, K; Conings, S; Annaert, P; Tibboel, D; Pfister, M; van Calsteren, K; van den Anker, JN; Dallmann, A
Abstract : Background: Little is known about fetal acetaminophen (paracetamol) pharmacokinetics and its potential for toxicity, despite the frequent use of acetaminophen during pregnancy. The aim of this study was to develop a feto-maternal physiologically based pharmacokinetic model (f-m PBPK) to predict placental transfer and PK of acetaminophen and its metabolites in fetus at term pregnancy. Methods: Previously, a pregnancy PBPK model was developed for prediction of maternal PK of acetaminophen and its metabolites. This model was structurally extended with the fetal liver, and quantitative information on the maturation of relevant enzymes was integrated. Three different approaches (ex vivo placenta perfusion experiments, scaling of passive diffusion transfer rates, and the Mobi® default method) to describe placental drug transfer were tested. Predicted maternal and fetal acetaminophen concentrations were compared with those observed in the literature. umbilical cord data at birth. Results: The 3 different approaches to predicted acetaminophen PK in the umiblical vein were found to yield broadly similar results. Acetaminophen exposure was similar in maternal blood compared to venous umbilical cord blood. Prediction of the median dose fraction of acetaminophen converted to its metabolites (fm ) revealed higher maternal acetaminophen-glucuronide formation clearance and sulphate formation compared to that in the fetal liver (fm _glucuronide 52.2 vs 0% and fm _sulphate 30.4 vs 0.8%, respectively) and higher fraction of acetaminophen converted to the reactive metabolite N-acetyl- p- benzoquinone-imine (fm _NAPQI, 6.5 vs 0.06%) in pregnant women compared to their fetus. Conclusion: No differences were observed in the 3 approaches for integration of placental drug transfer. Differences in acetaminophen biotransformation to its metabolites between pregnant women and their fetuses were quantitatively predicted. Disclosure(s): Paola Mian received a Short term Minor (STM-2017) grant from the Stichting Sophia Kinderziekenhuis fonds to conduct this research.